Design Of Intelligent Stick Based On Microcontroller With GPS Using Speech IC - Naseer Muhammad; Qazi Waqar Ali (International Journal of Electrical and Computer Engineering (IJECE), 2012)
For visually impaired persons the endeavors and researchers have spent the decades to develop an intelligent and smart stick to protect and alert them from obstacles. This paper proposes a new thought developing an intelligent stick equipped with GPS navigation system, which detect the obstacles in path and gives information about their location using GPS coordinates. The combination of ultrasonic sensors and GPS will detect the obstacles and determine the position and will gives information about location through Bluetooth.DOI:http://dx.doi.org/10.11591/ijece.v2i6.1622